Fraud trend in the regional government of Central Sulawesi province - Taufik Hidayat B. Tahawa; Nurhidayah Nurhidayah; Andi Ainil Mufidah Tanra; Riady Ibnu Khaldun (The Indonesian Accounting Review, 2020)
This study aims to analyze the effect of the Government Internal Control System and organizational commitment on the fraud trend in Regional Apparatus Work Units (SKPD) of Central Sulawesi Province both simultaneously and partially. The study used 43 people as the respondents from each Regional Apparatus Work Unit (SKPD). The data were collected by using questionnaires and analyzed using with multiple linear regression analysis tools and the statistical program SPSS version 20.0. The results show that the implementation of the government internal control system and organizational commitment has a significant effect on fraud trend. Based on the results of the f-test (simultaneously), government internal control system and organizational commitment have a significant effect on fraud trend. For the results of  the t-test (partially),  government internal control system and organizational commitment have a significant effect  on fraud trend. Based on the results of this research, this study suggests and recommends that  the Central Sulawesi government increase their understanding of the importance of the implementation of the government internal control system that has been regulated in Law Number 60 of 2008, given the need for a solid foundation such as a control system to minimize the occurrence of various acts of fraud.